Peningkatan Kemampuan Berpikir Kreatif Matematis Siswa Melalui Media Video Pembelajaran - Junaedi, Ahmad; Rosdianwinata, Eka; Pratidiana, Deni (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2024)
This research examines students' creative thinking in learning mathematics at the SMP/MTs level using video learning media. This research uses a quantitative approach with experimental methods. The respondents in this research were MTs YIU Pasirgadung students, where there were 19 people in class VIII A and 19 people in class VIII B. The aspects studied are related to students' creative mathematical thinking regarding the use of instructional video media in mathematics learning to improve students' mathematical creative thinking abilities. The research results showed that some students experienced an increase in creative thinking abilities after participating in learning using learning video media. These findings suggest the need for further research to explore more deeply the application of learning video media in improving students' creative thinking abilities. Thus, it is hoped that the use of learning video media can form students' creative thinking patterns in learning.